Healthcare, Frugal Innovation, and Professional Voluntarism - Ackers, Helen Louise. author. aut Link
XI, 141 p. 8 illus., 7 illus. in color.
Keywords: This book is open access under a CC BY 4.0 license. This book investigates what international placements of healthcare employees in low resource settings add to the UK workforce and the efficacy of the its national health system. The authors present empirical data collected from a volunteer deployment project in Uganda focused on reducing maternal and new-born mortality and discuss the learning and experiential outcomes for UK health care professionals acting as long term volunteers in low resource settings. They also develop a model for structured placement that offers optimal learning and experiential outcomes and minimizes risk, while shedding new light on the role that international placements play as part of continuing professional development both in the UK and in other sending countries.